The spatial characteristics of the infrastructural background of physical education (PE) classes in Hungarian kindergartens - Gábor KOZMA (Editura Universităţii din Oradea, 2020)
Kindergarten physical education (PE) plays an important role in the development of the age group concerned for a number of reasons; however, it is only possible in case of certain infrastructural conditions, which make it possible to have PE classes even in case of unfavourable weather conditions. In the spirit of the above, the primary objective of this paper is the examination of the spatial distribution of these facilities (smaller gym rooms and larger gyms) used for kindergarten PE classes in Hungary. The following could be emphasised from the research findings. Firstly, the infrastructural conditions of kindergarten PE are not very favourable in Hungary: hardly more than 50% of all institutions have suitable infrastructure. Secondly, from among the factors influencing the spatial distribution of the available facilities, at both the district and the settlement levels, the size of the population can be considered as particularly important: as the population size increases, an improvement of the conditions can be seen. Thirdly, the level of economic development hardly has any influence on their position.